Effect of immediate initiation of antiretroviral treatment on the risk of acquired HIV drug resistance. (28th January 2018) - Lodi, Sara; Günthard, Huldrych F.; Dunn, David; Garcia, Federico; Logan, Roger; Jose, Sophie; Bucher, Heiner C.; Scherrer, Alexandra U.; Schneider, Marie-Paule; Egger, Matthias; Glass, Tracy R.; Reiss, Peter; et al.
Abstract : Objective: We estimated and compared the risk of clinically identified acquired drug resistance under immediate initiation [the currently recommended antiretroviral therapy (ART) initiation strategy], initiation with CD4 + cell count less than 500 cells/μl and initiation with CD4 + cell count less than 350 cells/μl. Design: Cohort study based on routinely collected data from the HIV-CAUSAL collaboration. Methods: For each individual, baseline was the earliest time when all eligibility criteria (ART-naive, AIDS free, and others) were met after 1999. Acquired drug resistance was defined using the Stanford classification as resistance to any antiretroviral drug that was clinically identified at least 6 months after ART initiation. We used the parametric g-formula to adjust for time-varying (CD4 + cell count, HIV RNA, AIDS, ART regimen, and drug resistance testing) and baseline (calendar period, mode of acquisition, sex, age, geographical origin, ethnicity and cohort) characteristics. Results: In 50 981 eligible individuals, 10% had CD4 + cell count more than 500 cells/μl at baseline, and 63% initiated ART during follow-up. Of 2672 tests for acquired drug resistance, 794 found resistance. The estimated 7-year risk (95% confidence interval) of acquired drug resistance was 3.2% (2.8, 3.5) for immediate initiation, 3.1% (2.7, 3.3) for initiation with CD4 + cell count less than 500 cells/μl, and 2.8% (2.5, 3.0) for initiation with CD4 + cell count less than 350 cells/μl. In analyses restricted to individuals with baseline in 2005–2015, the corresponding estimates were 1.9% (1.8, 2.5), 1.9% (1.7, 2.4), and 1.8% (1.7, 2.2). Conclusion: Our findings suggest that the risk of acquired drug resistance is very low, especially in recent calendar periods, and that immediate ART initiation only slightly increases the risk. It is unlikely that drug resistance will jeopardize the proven benefits of immediate ART initiation. Abstract : Supplemental Digital Content is available in the text